OPTIMIZATION GEONFORMATION SYSTEMS FOR TASKS OF MONITORING OF ACOUSTIC POLLUTION - Зацерковний, В. І.; Оберемок, Н. В.; Бондарь, Ю. С.; Шерстюк, І. В. (Science-based technologies, 2016)
The main sources of acoustic contamination of an environment and the habitable areas, including the transport industry, the objects of industrial, the social and consumer industries, are considered. Gravity of these sources, during the acoustic contamination, varies widely for the different vities and residental area, however, the transport remains being primary and its shares is increasing continually. Due to the increase of megapolices and agglomeration, the intensive transport expansion and industry, the acoustic contamination problem is becoming global. Mainstreaming of modern high technologies in the industry, an expansion productivity of equipment, the usage of the multiple resources of land, air, railway water transports, common usage of various household electrical appliences-all these are leading to the repetitive contrarious noise, which a human suffers constantly being at work, in everyday life or on holidays. The main aspects of monitoring of enviromental acoustic contamination with the help of GIS and a modelling approach of this pollution. Geoinformation monitoring of acoustic contamination of the environmental and habitable areas are supposed to be considered as a complex system. The classification of geoinformation monitoring is studied, the structural scheme of system is demonstrated, the plots of town acoustic load are compiled, the result of experimental researched and mathematics modeling of noise levels from the different factors. The adaptation of available methods of noise mapping are put into practice. The state of town acoustic conditions on the base of created two-dimensional horisontal noise profile is analysed. The instructions for the recession of town acoustic load on the inhabitants are suggested.